Systematic Literature Review on Mathematical Representation: The Connection between Theories and Implementation - Putri, Amellia; Sujadi, Imam; Nursanti, Yuli Bangun; Nurhasanah, Farida (Universitas Muhammadiyah Surakarta, 2026)
Understanding and applying mathematical representation are essential in math education. However, many students face challenges in effectively using mathematical representation. Previous research has mainly focused on evaluating students' proficiency in mathematical representation rather than developing strategies to improve their skills. This has led to limited insights into research trends and information related to mathematical representation. Therefore, this SLR is crucial to fill the gap in the literature by providing a comprehensive overview of research trends on mathematical representation. This the study aims to analyze previous research related to mathematical representation, particularly the connection between the theories used, methodological features, the relationship between subjects and mathematical representation skills, as well as learning barriers and interventions to enhance these skills. At the end of the study, it was concluded that the relationship between all these variables was concluded. An examination of 52 scholarly papers on mathematical representation showed that most studies focus on assessing students' ability to use different types of mathematical representation to solve problems, drawing on theories proposed by Goldin and standards outlined by the National Council of Teachers of Mathematics (NCTM). The review also highlighted students' difficulties with mathematical representation and identified various methods for evaluating it, with written assessments and interviews being the most common approaches. Additionally, the review revealed numerous recommended activities to help students enhance their mathematical representation competency. In conclusion, the theoretical framework used in these studies significantly influences evaluation methods and recommended interventions in this field of study.